Construction of Islamic Character Education in Deli Malay Culture in Medan City - Hidayat, Rahmat; Hasballah, Zamakhsyari; Alfiansyah Siregar, Fandi (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
Malay Deli is one of the Malay sub-groups who live in Medan City. This tribe has awealth of cultural values which are used as a basis for the formation of the characterof its people. Malay Deli is one of the tribes that combines tradition and teachings fromIslam, this is in accordance with the philosophy in their lives "Adat Bersendi Syarak,Syarak Bersendi Kitabullah. Melalyu Deli people construct religious and culturalvalues through several stages, namely: (1) education; (2) Imitation; (3) Habituation;(4) Motivation; (5) Clarification and (6) Evaluation. The values constructed constructthe character of the Deli Malay community in the form of: (1) Religious; (2) Honest,(3) Tolerance; (4) Suave; (5) Be humble; (6) extroverted; (7) Likes to Help; (8)Prioritizing manners; and (9) respect for guests. This character makes them differentfrom other communities in the city of Medan